Christian Muslim relations. a bibliographical history - Thomas, David 1948-; Roggema, Barbara.; Monferrer Sala, Juan Pedro. (The History of Christian-Muslim Relations, 2015)
Christian-Muslim Relations. A Bibliographical History, volume 6 (CMR 6), covering the years 1500-1600, is a continuing volume in a history of relations between followers of the two faiths as it is recorded in their written works. Together with introductory essays, it comprises detailed entries on all the works known from this century. This volume traces the attitudes of Western Europeans to Islam, particularly in light of continuing Ottoman expansion, and early despatches sent from Portuguese colonies around the Indian Ocean. The result of collaboration between numerous leading scholars, CMR 6, along with the other volumes in this series, is intended as a fundamental tool for research in Christian-Muslim relations. Section editors: John Azumah, Clinton Bennett, Luis Bernabé Pons, Lejla Demiri, Martha Frederiks, John-Paul Ghobrial, David Grafton Stanisław Grodź, Alan Guenther, Abdulkadir Hashim, Şevket Küçükhüseyin, Andrew Newman, Gordon Nickel Claire Norton, Douglas Pratt, Peter Riddell, Umar Ryad, Davide Tacchini, Serge Traore, Carsten Walbiner